Pengaruh Penerapan Model Pembelajaran Kooperatif Tiper Word Square Terhadap Keaktifan Belajar PAI Siswa SMP N 3 Kinali - Ayu Azhari; Arifmiboy Arifmiboy; Iswantir M; Afrinaldi Afrinaldi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
During the PAI process, researchers saw that students did not play an active role during the learning process. Based on this problem, the aim of conducting this research is to find out how much influence the application of the Word Square type cooperative learning model has on the PAI learning activity of students at SMP N 3 Kinali. In this research, the type of research used by researchers is experimental research. From this experimental research, the researcher took a Quasi experimental design. The design is a Posttest Only Control design. Based on the results of the analysis of students' PAI learning activeness during the learning process by implementing the Word Square type cooperative learning model. In the learning process, students were seen paying attention and listening to the explanations given by the researcher and actively asking questions. The average result is 81.13. After data collection, it is then processed and hypothesis tested using the t-test. At the significant level α = 0.05. Test criteria: Accept Ha if tcount ≥ ttable and Reject H0 if tcount ≤ ttable. The results of hypothesis testing using the t-test show that the tcount value (21.5030) is greater than ttable (1.999). So, H1 is accepted, namely that there is an influence of implementing the Word Square type cooperative learning model on students' active PAI learning.